Patellar Resurfacing: Does It Affect Outcomes of Distal Femoral Replacement After Distal Femoral Resection?. (6th April 2016) - Etchebehere, Mauricio; Lin, Patrick P.; Bird, Justin E.; Satcher, Robert L.; Moon, Bryan S.; Yu, Jun; Li, Liang; Lewis, Valerae O.
Abstract : Background: Patellar resurfacing after routine arthroplasty remains controversial. Few studies have specifically examined the effect of patellar resurfacing on outcomes after resection of the distal part of the femur and reconstruction with a megaprosthesis. Our objective was to compare the outcomes of megaprosthesis reconstructions of the distal part of the femur with and without patellar resurfacing after resection of a distal femoral tumor. Methods: We retrospectively reviewed the clinical records of patients with a femoral tumor who underwent resection of the distal part of the femur and endoprosthetic reconstruction between 1993 and 2013. We excluded patients who had had extra-articular knee resection, patellectomy, revision, reconstruction with an expandable prosthesis, or a proximal tibial replacement associated with the distal femoral replacement. We compared demographic characteristics, surgical variables, anterior knee pain, range of motion, extensor lag, Insall-Salvati ratio, Insall-Salvati patellar tendon insertion ratio, impingement, patellar degenerative disease, additional patellar procedures, complications, and Musculoskeletal Tumor Society (MSTS) score between the patellar resurfacing and nonresurfacing groups. Results: One hundred and eight patients—sixty without patellar resurfacing and forty-eight with patellar resurfacing—were included in the study. The mean age was 33.9 years (range, twelve to seventy-five years). There were fifty-four men and fifty-four women. The mean duration of follow-up was 4.5 years (range, 0.7 to twenty years). There was no significant difference in anterior knee pain between the groups (p = 0.51). Anterior knee pain did not significantly affect the range of motion, extensor lag, or reoperation or complication rate. Patellar degenerative disease occurred in 48% of the nonresurfaced knees but was not associated with focal pain. Complication rates were similar in the two groups, although peripatellar calcifications were significantly more common in the resurfacing group (19% versus 2%; p = 0.005). There was no significant difference in the mean MSTS score between the nonresurfacing (81%) and resurfacing (71%) groups (p = 0.34). Conclusions: There were no differences in anterior knee pain, range of motion, extensor lag, or MSTS score between the patients with and those without patellar resurfacing. There were no cases of patellar component loosening or revision. In light of the similar outcomes in the two groups, the decision to resurface should be left up to the individual surgeon, who should take into account preoperative peripatellar pain and the status of the patella at the time of resection. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.